Metode Pembelajaran Taḥfīẓ Al-Quran Dalam Meningkatkan Hafalan Siswa Kelas VIII Di Pondok Pesantren Imam Bukhari Putri Selokaton, Gondangrejo, Karanganyar - Nurjannah, Ita, Drs. Arief Wibowo, M.Ag (2016)
Imam Bukhari Islamic Boarding School of Selokaton is a boarding school performing salafiyah education program as a compulsory nine year education with superior program of Taḥfīẓ Al-Quran and Arabic conversation. Based on the background, purpose of the research is to know learning method of Taḥfiẓ Al-Quran in improving memorization of female students of class VIII in Imam Bukhari Islamic Boarding School and to know what are supporting and inhibiting factors in the process of learning. The research is a field research with descriptive-qualitative method. Data of the research have been obtained by using techniques of observation, interview and documentation and then have been analyzed. Based on results of the research, it can be concluded that methods of learning using in Imam Bukhari Islamic Boarding School for female students are: 1) audio/talaqqī (classical), namely a teacher reads a verse and students resound it over and over until they are able to memorize it correctly; 2) kitābah method, namely students perform memorization test. The students are asked to complete an incomplete written verse; 3) waḥdah method, namely to memorize of only one verse at a time until it can be memorized correctly, if a student cannot memorize it correctly, she will not be allowed to go to further verse; and 4) murāja'ah. method, it means to repeat. Murāja'ah method is divided into three methods: sabaq, students submit new memorization; sabqi, students submit yesterday memorization; and manzil students submit memorization that they have performed for long time. Then, there are weekly activities called as tasmī', akbar and aṣgar are also conducted. Supporting factors of the learning process were: ustażah (female teachers) provide motivation, advice and remind students to ignore boredom or laziness in memorizing Al-Quran. The inhibiting factors are intensive activities, many school works, and less-supporting environment.